2022
DOI: 10.3389/fenvs.2022.823838
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Interactions in Environmental Regulation: Evidence From Spatial Effects Across Chinese Cities

Abstract: Developing countries are notorious for their enforcement gap in environmental regulation. Despite policymakers and scholars focusing on this phenomenon in China, there is little literature to explore the cause for its prevalence. This paper aims to explain this occurrence from the perspective of strategic interactions among the local governments in China based on the yardstick competition theory. Employing spatial panel data models, we use a panel dataset of Chinese cities to investigate strategic interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
(88 reference statements)
1
0
0
Order By: Relevance
“…From a spatial perspective, the behavioral preferences of local governments in the YRD region between EGC and ER had spatial agglomeration characteristics. This finding indicates that there may be an imitation effect among local governments, which is consistent with the findings of Zhang et al [ 65 ] and Pan et al [ 66 ]. In addition, we found that the behavioral preferences of local governments showed the characteristics of large-scale agglomeration in the first three periods and diversification and small-scale agglomeration in the last three periods.…”
Section: Discussionsupporting
confidence: 92%
“…From a spatial perspective, the behavioral preferences of local governments in the YRD region between EGC and ER had spatial agglomeration characteristics. This finding indicates that there may be an imitation effect among local governments, which is consistent with the findings of Zhang et al [ 65 ] and Pan et al [ 66 ]. In addition, we found that the behavioral preferences of local governments showed the characteristics of large-scale agglomeration in the first three periods and diversification and small-scale agglomeration in the last three periods.…”
Section: Discussionsupporting
confidence: 92%